A realidade aumentada aplicada ao conceito de caderneta de cromos - Luís Miguel Nunes da Costa (2015)
Museums are a centrepiece of cultural heritage, but they need to enhance interactive media in order to follow the recent technological developments and attract a younger audience. This work focus on traditional Portuguese boats as an ex-libris of the Portuguese history, namely in museums with a maritime dimension. The aim of this research is to develop an application that will enable uncovering boats' features in a most engaging way. To this purpose it is used a gamified approach based on stickers and augmented reality. The research questions to be addressed are the following: (1) What technology combination best fits museums? (2) What virtual and augmented reality techniques should be used without interfere with museum pieces? (3) What are the most effective gamification strategies in this type of approach? (4) How is it possible to match museums and technologies in a digital collecting view? Therefore, it is developed a digital sticker album based on gamification principles. Collecting is the mechanical basis, where this application will retrieve access to a digital sticker when a particular feature is identified on a boat, through augmented reality. Thus, in a museum context, digital stickers are gathered when challenges are overcome, which in turn triggers mixed reality information such as three-dimensional modelling, text and videos. After this specific experience in the museum, a digital sticker album will unlock 3D models of the boats that were linked to the accomplished stickers that corresponds itself to a tangible reward such as a souvenir. Keywords: collecting, gamification, museums, augmented reality, virtual reality